Jewish law and ethics: The case of the revolving door - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2022)
What is ethics and how is it related to the legal system and to economics? Are there ethical values in Jewish Law, and could it be that we find in the writing of Hazal [the sages] an interest in job turnover? The purpose of this paper is to answer to those questions by focusing on a specific element of our economic life: the revolving door.
Keywords: H10; H70; O11; O43; 330; corruption; ethics; legal system; revolving door; social norms